PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENUMPANG KERETA COMMUTER LINE DI STASIUN KALIDERES - Nur Cholis; Robby Irvawan (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determinethe influenceof service quality to customer satisfaction of Commuter Line at Kalideres station. Population of this study is some customers deemed to represent the entire population as respondentacquired from data of about 1,000 customers depart from and arrive at Kalideresstation in March 2021. 136 respondents are used as sample based on slovin formula because the sample of study is accidental sampling. Data is collected by questionnaire using likert scale. This study is analyzed by data quality test (validity and realiability tests), classical assumption test, linear regression analysis, hypothetical test (T and F tests), moment product correlation, and coefficient of determination using SPSS 25. Collected data shows that service quallity affects significantly to customer satisfaction of Commuter Line at Kalideres station as shown by R square value by 0.316 which means that service quality can indicate customer satisfaction variable of Commuter Line at Kalideresstation by 31.6% while the remaining 68.4% is indicated by another variable which is not explained in this study by the writer. The conclusion of this study is the better service quality provided to customers, the effect will be on customer satisfaction in using Commuter Line. It is recommended that the provider of transportation considers safe, comfortable access to station for customers in addition to service quallity inside the station.